2004
DOI: 10.2135/cropsci2004.1593
|View full text |Cite
|
Sign up to set email alerts
|

Grain Composition and Productivity of Maize Hybrids Derived from the Illinois Protein Strains in Response to Variable Nitrogen Supply

Abstract: The Illinois Long‐Term Protein Selection strains of maize (Zea mays L.) have been employed in a variety of studies investigating the genetic and physiological control of maize grain composition. These prior studies, however, have not assessed the grain composition and yield potential of these strains in hybrid combinations with an elite tester, or in response to supplemental N. Our objective was to study the interactive effect of genotype and N supply on productivity and grain quality for hybrids with a wide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
79
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 17 publications
(26 reference statements)
10
79
1
4
Order By: Relevance
“…In Uribelarrea et al found that abundant nitrogen supply stimulated protein synthesis in high protein genotypes and that protein and oil had a positive correlation. However, reported that higher inputs of nitrogen did not result in higher protein in maize in the conventional cropping system [3]. In both years, the hybrid has more SPC when applied with urea and AS than CAN resulting in N-source × genotype interaction (Table 6).…”
Section: Seed Protein Contentmentioning
confidence: 94%
See 4 more Smart Citations
“…In Uribelarrea et al found that abundant nitrogen supply stimulated protein synthesis in high protein genotypes and that protein and oil had a positive correlation. However, reported that higher inputs of nitrogen did not result in higher protein in maize in the conventional cropping system [3]. In both years, the hybrid has more SPC when applied with urea and AS than CAN resulting in N-source × genotype interaction (Table 6).…”
Section: Seed Protein Contentmentioning
confidence: 94%
“…Grain quality is a major issue especially in low input farming systems. Assimilate supply can be altered by N availability and by genotype, and that both can effect yield and grain composition [3]. Grain composition is a result of the genetic make-up of the endosperm sink, the maternal plant, and the environment [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations